Does Workplace Matter? How Engineers Use and Access Information Resources in Academic and Non-Academic Settings. Issue 3 (3rd July 2019) - Kaufman, Jordan; Tenopir, Carol; Christian, Lisa
ABSTRACT: The ways in which engineers seek, read, and use information resources varies depending on their workplace. This study seeks to provide an understanding of how engineers in academia and engineers in other workplaces seek and use information resources and how those differ. For example, the researchers found that engineers in academia consider journal articles essential to their work, while engineers in other workplaces value standards over journal articles. By understanding that the workplace effects engineers' information seeking needs, librarians can better meet the needs of engineers in a variety of workplace settings.